2023
DOI: 10.1007/s00277-023-05222-5
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline as salvage treatment of febrile neutropenia in patients with haematological malignancies—a retrospective single-centre analysis of 200 cases

Abstract: Tigecycline has been used to treat patients with febrile neutropenia (FN). This study aims to analyse the effectiveness of tigecycline as salvage treatment of FN. Patients records from 09/2004 to 04/2019 were reviewed. Cases were eligible if fever persisted/recurred (p/r-FN) after 3 days of second-line treatment with a carbapenem, and were divided into three groups: switch to tigecycline (TGC group), switch to other antibiotics (OAB group), and no switch (W&W group). The primary endpoint was response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…While there are some studies on the use of tigecycline in hematologic malignancy patients, almost none have identified resistance genes. Some reports suggest that susceptibility to tigecycline is favorable in carbapenem strains with a higher MIC [93][94][95], but the clinical outcomes are not consistent [96][97][98]. One study indicates that combining piperacillin/tazobactam with tigecycline is considered safe and more effective compared to using piperacillin/tazobactam by itself in febrile neutropenic hematologic cancer patients at high risk [99].…”
Section: Tigecyclinementioning
confidence: 99%
“…While there are some studies on the use of tigecycline in hematologic malignancy patients, almost none have identified resistance genes. Some reports suggest that susceptibility to tigecycline is favorable in carbapenem strains with a higher MIC [93][94][95], but the clinical outcomes are not consistent [96][97][98]. One study indicates that combining piperacillin/tazobactam with tigecycline is considered safe and more effective compared to using piperacillin/tazobactam by itself in febrile neutropenic hematologic cancer patients at high risk [99].…”
Section: Tigecyclinementioning
confidence: 99%